2003
DOI: 10.1258/135763303767149951
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with telemedicine presentation at a multidisciplinary tumour meeting among patients with head and neck cancer

Abstract: Patients with head and neck cancer in the western part of Sweden are presented at a multidisciplinary tumour (MDT) meeting held once a week at the regional hospital in Göteberg. During a 13-month study period, 58 patients were presented via telemedicine; 45 of these patients (78%) answered a questionnaire. A face-to-face control group (the FTF group, n=46) comprised patients from district hospitals not using telemedicine. These patients travelled to Göteberg for the MDT meeting; 39 of them (85%) answered the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Studies reporting patient satisfaction as a percentage of total patients found 80% to 96% of patients to be satisfied with an asynchronous model and 95% to 100% of patients satisfied with a synchronous model. 17,[26][27][28][29][30]32,34 Notably, of the five studies included that assessed synchronous models based on percent satisfied, three reported 100% satisfaction (aggregate n = 97). 28,30,32 Three studies reported patient satisfaction on numerical scales, one citing an average score of 8/10 with an asynchronous model and the others reporting scores of 5.7/6 and 9.5/10 with synchronous models.…”
Section: Patient and Provider Satisfactionmentioning
confidence: 99%
“…Studies reporting patient satisfaction as a percentage of total patients found 80% to 96% of patients to be satisfied with an asynchronous model and 95% to 100% of patients satisfied with a synchronous model. 17,[26][27][28][29][30]32,34 Notably, of the five studies included that assessed synchronous models based on percent satisfied, three reported 100% satisfaction (aggregate n = 97). 28,30,32 Three studies reported patient satisfaction on numerical scales, one citing an average score of 8/10 with an asynchronous model and the others reporting scores of 5.7/6 and 9.5/10 with synchronous models.…”
Section: Patient and Provider Satisfactionmentioning
confidence: 99%
“…4 Telemedicine is highly relevant to delivery of cancer services in Scotland in areas remote from teaching centres which have low population densities. 5 A number of studies attest to the feasibility and acceptability of telemedicine-linked MDT meetings in oncology [6][7][8][9] for a variety of cancers, including breast, 10 head and neck, 11 gynaecological, 12,13 lung 10,14 and colorectal cancer. 10 Health professionals are generally supportive of telemedicine [15][16][17] and of tele-oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Although no prior studies have evaluated real‐time teleconferencing for treatment planning and preoperative discussion, other components of telemedicine have been utilized in otolaryngology patients. Patients with head and neck cancer have been presented remotely at multidisciplinary tumor boards with high diagnostic accuracy, patient satisfaction, and potential cost savings . Secure text messaging and surveys have enabled support for patients as they undergo treatment for head and neck cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been proposed as a mechanism to facilitate treatment of head and neck cancer . To date, telemedicine has been used to remotely present patients with head and neck cancer at multidisciplinary tumor boards and provide guidance via secure text messaging as patients undergo treatment . To our knowledge, no prior studies have evaluated the role of telemedicine in remote presurgical evaluation, workup, and counseling for patients with head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%